Evaluation of the relationship between serumsVisfatin and Resistin levels with BMI in PCOS young women - Farshchian, Fatemeh; Kazeruni, Faranak; Ramezani Tehrani, Fahimeh; Parsian, Hadi; Namaki, Saeed; Amirrasouli, Houshang; Moslemi, Azam; Rahimipour, Ali (Archives of Advances in Biosciences, 2014)
Polycystic ovary syndrome (PCOS) is a common endocrine / metabolic disorder in women of reproductive age .Abdominal adiposity and obesity are frequently present in PCOS. It now appears that, obesity is associated with a low-grade inflammation of white adipose tissue. Adipokines play a significant role in the pathogenesis of a low-grade inflammation associated with obesity. Among variety of adipokines, resistin and visfatin are proposed as important pro inflammatory mediators and they have recently been suggested to be associated with obesity related diseases.The aim of this study is to evaluate the correlation of visfatin and resistin serum levels and the ratio of these two adipokines with BMI in PCOS women under age of 35 years old. Twenty eight young women with clinically confirmed PCOS disease (14 lean and 14 obese), and 12 young, healthy and lean women with stable weight and BMI<25 were enrolled. Blood was obtained from the included persons, and visfatin and resistin were assessed by ELISA method. We did not observe any significant differences in serum visfatin and resistin concentrations and also in the Visfatin/Resistin ratio between PCOS and control group. Also we did not found a significant correlation between visfatin and resistin with BMI. This study demonstrated that serum resistin and visfatin levels do not seem to be directly involved in the pathology of PCOS.